Development for a better life - Epure, Manuela (Journal of Economic Development, Environment and People, 2015)
Today, humanity is facing various challenges when it comes to the development level in different countries or regions. The global economy is bouncing back from a serious crisis, yet still struggling with the unpredictable reminiscences of the crisis. Restarting the economic growth is vital for the global development. But when it comes to “development”, are we sure what it really means with respect to different countries? World Bank experts define development through a set of indicators of wealth which reflect mainly the quantity of resources, resource allocation, the effect of production and consumption on people’s environment and the like. Different countries have different visions on how to increase the national wealth, therefore the interest in setting development policies may vary from region to region, from country to country. Development is also related directly to people’s quality of life: access to education and health care services, employment opportunities, availability of clean air and safe drinking water, and the threat of crime and so on. A sustainable economic growth must be nourished by the fruits of human development such as improvements in human capital along with opportunities for its efficient use: more and better jobs, better conditions for encouraging new and innovative business and greater democracy at all levels of decision‐making[1]. The interdependency between sustainable economic growth and human development is more than obvious, complex and diverse relationships are constantly set, the prerequisites for economic growth or human development are established, and the list is still open. Investing in human capital development is one of the conditions that enable economic growth. [1] SoubottinaT.P., Sheram K.‐ Beyond Economic Growth –Meeting the Challenges of Global Development, World Bank Learning Resources Series, USA, 2000 http://www.worldbank.org/depweb/beyond/beyondco/beg_00.pdf